Advances in responsive liquid metal composites for cancer therapy. (March 2023) - Yang, N.; Gong, F.; Ge, J.; Wang, L.; Wang, G.; Cheng, L.
Abstract: Liquid metal (LM), with high electrical/thermal conductivity, excellent mechanical capacity, and extraordinary fluidity, has emerged as a promising class of functional material. Owing to their fascinating optical, magnetic, and electrical properties and good biocompatibility, LM and its composites have been widely explored in the field of cancer therapy. In this review, we intend to present an overview of advances in responsive LM composites for cancer therapy. According to their responsive modes, we mainly classify and summarize the response into two types: exogenous response, including light, ultrasound, microwave, radiofrequency, X-ray, electric field, and magnetic field, and endogenous stimuli, including the tumor microenvironment (TME) response, such as acidic pH value, high level of H2 O2, and glucose. The representative responsive LM and their composites are analyzed and discussed from the aspects of the rational design and construction of LM composites, the principles of the chemical response, and the mechanism of tumor therapy. Finally, the challenges and perspectives of LM composites for cancer therapy are also discussed. This timely review would be beneficial to the application of responsive LM composites in cancer therapy. Highlights: Liquid metal (LM) with unique physical/chemical properties have attracted tremendous attention in biomedical applications. The stimuli-responsive treatment based on LM composites have designed for highly effective cancer therapy. The representative applications of the response LM composites are discussed and summarized. This timely review will be beneficial to the bioapplication of responsive LM composites.